The effectiveness for complications prevention in essential hypertensive patients, Bang Sai district, Ayutthaya province (Thai) - Komrattanapanya, Krongthong; Khamrat, Chaiyong; Dejthai, Thonglaw (Asia-Pacific Journal of Science and Technology, 2017)
This quasi-experimental research study aimed to examine and compare knowledge of hypertension, perceptions of complications, and practices for complication prevention of essential hypertension patients in Bang Sai District, Phra Nakhon Si Ayutthaya Province. The study was conducted by applications of Health belief model theory, Social support theory, and Demming’s quality cycle for organization of activities. The sample consisted of 70 patients purposively selected according to the established requirements : patients at Amphoe Bang Sai hypertension clinic, aged 40 years and older with hypertension levels ranging 120/80-160/95 mmHg, and without complications. Thirty-five patients were assigned into an experimental group receiving organization of complication prevention activities for 12 weeks, and the other 35 patients were assigned into a comparison group. Data were collected twice, before and after the experiment using a questionnaire. The collected data were analyzed using percentage, mean, standard deviation, paired samples t-test, and independent samples t-test. The study findings revealed that after the experiment the experimental group had a mean score on knowledge of hypertension condition, perceptions of severity, perceptions of risk opportunity to generate complications, perceptions of usefulness of practice for complication prevention, and practice for complication prevention at a high level; increased from before the experiment, and significantly higher than the comparison group (p<0.05). Therefore, the mentioned model should be supported to apply to other communities with demographic characteristics and contexts close to one another in the future.